IMPROVEMENT OF WRITING SKILL OF PANTUN USING THE FIELDTRIP METHOD FOR ELEMENTARY SCHOOL STUDENTS - Aprima Vista; Darnis Arief (JURNAL PAJAR (Pendidikan dan Pengajaran), 2020)
This research is motivated by the low ability in writing Pantun for elementary school students. The purpose of this study was to determine the improvement of the ability to write pantun for elementary school students using the field trip method. This research was a classroom action research carried out in grade 5 of SDN 01 Nan Sabaris, Padang Pariaman Regency consisting of 30 students. The research procedure consisted of planning, implementing, observing, and reflecting. Data collection techniques used the method of observation, measurement of learning test results and documentation. Data analysis techniques consisted of quantitative data. Quantitative data used to analyze the results of the ability to write Pantun by measuring the percentage of mastery learning and class average. The results showed that the students' initial ability score in writing rhymes was 67.00, cycle I got a score of 72.00, and cycle II got a score of 83.00. This research proved that there was an increase in the ability to write rhymes for elementary school students using the field trip method. The implication of this research is to be used as a reference for teachers in implementing the learning process of Pantun writing for elementary school students.